Projectively Cohen-Macaulay surfaces of small degree in P^5 - Marina Mancini (Le Matematiche, 2000)
In this paper we consider the nondegenerate projectively Cohen-Macaulay (p.C.M.) surfaces of small degree in P^5 . We determine those of degree d ≤ 9  and all candidate rational surfaces as p.C.M. surfaces.